2012
DOI: 10.1177/030089161209800415
|View full text |Cite
|
Sign up to set email alerts
|

Patient Dignity Inventory (PDI) Questionnaire: The Validation Study in Italian Patients with Solid and Hematological Cancers on Active Oncological Treatments

Abstract: The Italian version of PDI is a valid and reliable tool to evaluate the dignity related-distress in out-patients with solid and hematological cancers, on active oncological treatments, in non advanced stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
2
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(101 citation statements)
references
References 36 publications
7
73
2
19
Order By: Relevance
“…The Cronbach's alpha coefficient for the PDI-CZ was high (0.92) and provides evidence that this 25-item inventory had very good internal consistency. This result suggests appropriate internal consistency among items, in agreement with other published PDI validation studies (Chochinov et al 7 [0.93]; Ripamonti et al 9 [0.96]; Sautier et al 11 [0.96]; Avestan et al 12 [0.92]; and Rull an et al 13 [0.89]). A reliability coefficient range is considered acceptable between 0.7 and 0.9.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The Cronbach's alpha coefficient for the PDI-CZ was high (0.92) and provides evidence that this 25-item inventory had very good internal consistency. This result suggests appropriate internal consistency among items, in agreement with other published PDI validation studies (Chochinov et al 7 [0.93]; Ripamonti et al 9 [0.96]; Sautier et al 11 [0.96]; Avestan et al 12 [0.92]; and Rull an et al 13 [0.89]). A reliability coefficient range is considered acceptable between 0.7 and 0.9.…”
Section: Discussionsupporting
confidence: 89%
“…Our 14-day test-retest interval was similar to the study conducted by Ripamonti et al (Lin concordance correlation coefficient ¼ 0.73). 9 Higher values were confirmed in the studies by Chochinov et al 7 (the retest one day later [r ¼ 0.85]) and Rull an et al 13 (the retest two days later [intercorrelation coefficient ¼ 0.93]). The authors concluded that this shorter time interval was appropriate because significant variations were not expected, and the patients would not be able to recall the answers.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Regarding the PDI‐IT, we opted for the validation obtained from our previous study, because of its specificity for end‐of‐life patients, and for the presence of the ED subscale. It differs from previous Italian validations in the oncological setting because they present different factor structures and are referred to advanced and nonadvanced cancer patients and patients with active oncological treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Existential concerns may represent a strong risk factor for the maintenance of terminally ill patients' well‐being, and several of them are included in Chochinov et al's dignity model . In fact, loss of dignity and existential distress are associated …”
Section: Introductionmentioning
confidence: 99%